2019
DOI: 10.1177/0003319719842682
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Incidence of Thromboembolic Events in Takotsubo Syndrome as Compared With Acute Coronary Syndrome

Abstract: Thromboembolic events are a common complication in Takotsubo syndrome (TTS). However, their long-term incidence compared with acute coronary syndrome (ACS) is lacking. In-hospital and long-term incidence of thromboembolic events of 138 consecutive patients with TTS were compared with 138 sex- and age-matched patients with ACS. Predictors of events were analyzed. The incidence of thromboembolic events in TTS was 2-fold higher than ACS (21% vs 9%; P < .01) over a mean follow-up of 5 years. Although the left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The rate of thromboembolic events in our population was substantially lower than that recently observed in a single-centre study by El-Battrawy et al, who reported a prevalence of 13.0% (18 of 138 patients) during hospitalization. 5 Conversely, our findings are largely consistent with the results from the multicentre German Italian Stress Cardiomyopathy (GEIST) Registry, which reported a prevalence of 2.2% (12 of 541 patients). 6 The incidence of stroke at follow-up was not investigated in our study, which considered the occurrence of major adverse cardiac events as the composite study endpoint.…”
Section: Predictors Of Thromboembolic Events In Takotsubo Syndrome: Rsupporting
confidence: 91%
“…The rate of thromboembolic events in our population was substantially lower than that recently observed in a single-centre study by El-Battrawy et al, who reported a prevalence of 13.0% (18 of 138 patients) during hospitalization. 5 Conversely, our findings are largely consistent with the results from the multicentre German Italian Stress Cardiomyopathy (GEIST) Registry, which reported a prevalence of 2.2% (12 of 541 patients). 6 The incidence of stroke at follow-up was not investigated in our study, which considered the occurrence of major adverse cardiac events as the composite study endpoint.…”
Section: Predictors Of Thromboembolic Events In Takotsubo Syndrome: Rsupporting
confidence: 91%
“…Prognosis should be evaluated case by case, depending on the presence of concomitant factors. For example, for thromboembolic events as reported by El-Battrawy et al 9 Also, males seem to have a higher mortality risk.…”
mentioning
confidence: 82%
“…The incidence of thromboembolic events in TTS was 2-fold higher than for ACS (21% vs 9%; P < .01) over a mean follow-up of 5 years. 9 Although TTS has been generally considered as a benign disease since left ventricular function returns to normal within a short time, contemporary observations have modified this assumption. 10 A recent meta-regression study including 54 studies (>4600 patients) reported a death during admission of 1.8%, and a 3.5% annual all-cause mortality.…”
mentioning
confidence: 99%
“…Time of LV thrombi formation ranges from admission until 2 weeks after. Apical ballooning pattern, left ventricular ejection fraction ≤ 30%, previous vascular disease, increased C-protein levels, troponin-I levels > 10 ng/mL, and a white blood cell count on admission > 10 × 10 3 cells/μL are independent predictors of LV thrombosis [ 28 , 29 , 30 ].…”
Section: Acute Treatment In Takotsubo Syndrome (Tts)mentioning
confidence: 99%